Potential of Host Serum Protein Biomarkers in the Diagnosis of Tuberculous Meningitis in Children - Manyelo, Charles M.; Solomons, Regan S.; Snyders, Candice I.; Mutavhatsindi, Hygon; Manngo, Portia M.; Stanley, Kim; Walzl, Gerhard; Chegou, Novel N. (Frontiers in Pediatrics, 2019)
Background: Tuberculous meningitis (TBM) is the most severe form of tuberculosis and results in high morbidity and mortality in children. Diagnostic delay contributes to the poor outcome. There is an urgent need for new tools for the rapid diagnosis of TBM, especially in children. Methods: We collected serum samples from children in whom TBM was suspected at a tertiary hospital in Cape Town, South Africa. Children were subsequently classified as having TBM or no TBM using a published uniform research case-definition. Using a multiplex cytokine array platform, we investigated the concentrations of serum biomarkers comprising biomarkers that were previously found to be of value in the diagnosis of adult pulmonary TB (CRP, SAA, CFH, IFN-γ, IP-10, Apo-AI and transthyretin) plus other potentially useful host biomarkers as diagnostic candidates for TBM. Findings: Out of 47 children included in the study, 23 (48.9%) had a final diagnosis of TBM and six were HIV infected. A modified version of the adult 7-marker biosignature in which transthyretin was replaced by NCAM1, diagnosed TBM in children with AUC of 0.80 (95% CI, 0.67-0.92), sensitivity of 73.9% (95% CI, 51.6-89.8%) and specificity of 66.7% (95% CI, 44.7-84.4%), with the other six proteins in the signature (CRP, IFN-γ, IP-10, CFH, Apo-A1 and SAA) only achieving and AUC of 0.75 (95% CI, 0.61-0.90) when used in combination. A new childhood TBM specific 3-marker biosignature (adipsin, Aβ42 and IL-10) showed potential in the diagnosis of TBM, with AUC of 0.84 (95% CI, 0.73-0.96), sensitivity of 82.6% (95 CI, 61.2-95.0%) and specificity of 75.0% (95% CI, 53.3-90.2%) after leave-one-out cross validation. Conclusion: A previously described adult 7-marker serum protein biosignature showed potential in the diagnosis of TBM in children. However, a smaller childhood TBM-specific 3-marker signature demonstrated improved performance characteristics. Our data indicates that blood-based biomarkers may be useful in the diagnosis of childhood TBM and requires further validation in larger cohort studies.